Genetic base and coefficient of parentage of rice (Oryza sativa) varieties released in Kerala - SHIVKUMAR, SHIVKUMAR; RAO, L SUBBA; RAM, T; MAJUMDER, N D; PADMAVATHI, G; RAO, U PRASADA; KRISHNAIAH, K (The Indian Journal of Agricultural Sciences, 2013)
An examination of the pedigrees of 29 rice (Oryza Sativa L.) varieties of hybrid origin, released in Kerala during'1966-95, revealed a narrow genetic base, as only 37 ancestors were used directly or indirectly in their developmentOut of 37 ancestors, 10 ancestors contributed 74.14% of the genetic base, Similarly. the cytoplasmic diversity wasalso limited, as 41.38% varieties could be 'traced back maternally to the same ancestor 'Ptb 10' ('Thekkancheera') and'thus probably carried its cYtoplasm, 'Dee Goo Woo Gen' (DGWG) was the most frequently appeared ancestor (96,55%)due to its dwarling gene (sdl), All the ,29 varieties except 'Kayamkulam I' were interrelated with an average coefficientof parentage of 0.137 for 406. combinations of 29 varieties.